Reliability assessment of confinement models of carbon fiber reinforced polymer-confined concrete. (June 2016) - Huang, Liang; Gao, Chang; Yan, Libo; Kasal, Bohumil; Ma, Gao
This paper presented a review of 84 confinement strength models developed for predicting the ultimate compressive strength of carbon fiber-reinforced polymer-confined concrete subjected to uniaxial compression. Among these models, 64 design-oriented models and 12 analysis-oriented models were selected and evaluated by a comprehensive database including the experimental results of 1475 carbon fiber-reinforced polymer-confined concrete specimens through three statistical indicators: the mean ( μ ), the coefficient of determination( R 2 ), and the root mean square error ( σ ) of the predicted ultimate compressive strengthf cc * and the experimental ultimate strengthf cc . Based on the results of evaluation, 27 design-oriented models were further considered for reliability assessment and structural reliability analysis. Given the performance of strength predictions and the reliability assessment, it was found that for the design purpose, the 27 design-oriented models are reliable for practical predictions of carbon fiber-reinforced polymer-confined concrete structures subjected to uniaxial compression.